70 A methodological approach of evidence synthesis to improve childhood cancer health outcomes and resource use in Egypt. (18th July 2022) - Soliman, Ranin; Elhaddad, Alaa; Eweida, Wael; Oke, Jason; Heneghan, Carl
Abstract : Objectives: There is a need to better target resources to improve care and outcomes based on evidence for children with cancer in Egypt. However, there is paucity of data about childhood cancer health outcomes (survival) and resource use in Egypt, and an identified gap in published evidence. In this study, we present a methodological approach to generate evidence about childhood cancer health outcomes and resource use in Egypt, and help make informed decisions to improve care and outcomes based on evidence. Method: We reflected on principal evidence-based medicine (EBM) concepts and the CEBM levels of evidence, as a reference to generate and assess high-quality evidence. Results: The proposed methodological approach/roadmap includes generating the evidence-base and identifying priority area(s) from local context in Egypt through: (1) determining survival rates and trends in survival; (2) determine resource use and costs childhood cancer treatment; (3) determine cost-effectiveness of childhood cancer treatment in Egypt and determine areas for potentail improvement; (4) generate curently best avaibale evdience from the literature about a priority area from local context, cost-effectiveness of treatment for relpased/refractory acute leukemia in children; (5) finally, underatnd the clinicians' perceptions on barriers and facilitators to implement cost-effective interventions based on evdience, to help translate knowledge into practice. Conclusions: The presented roadmap for evidence synthesis will generate high-quality evidence about childhood cancer outcomes and resource use in Egypt that is relevant to local context. This shall drive evidence-based improvements in childhood cancer care and outcomes in Egypt.